If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -2x)(1 + 2x) = 0 Multiply (1 + -2x) * (1 + 2x) (1(1 + 2x) + -2x * (1 + 2x)) = 0 ((1 * 1 + 2x * 1) + -2x * (1 + 2x)) = 0 ((1 + 2x) + -2x * (1 + 2x)) = 0 (1 + 2x + (1 * -2x + 2x * -2x)) = 0 (1 + 2x + (-2x + -4x2)) = 0 Combine like terms: 2x + -2x = 0 (1 + 0 + -4x2) = 0 (1 + -4x2) = 0 Solving 1 + -4x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4x2 = 0 + -1 -4x2 = 0 + -1 Combine like terms: 0 + -1 = -1 -4x2 = -1 Divide each side by '-4'. x2 = 0.25 Simplifying x2 = 0.25 Take the square root of each side: x = {-0.5, 0.5}
| ln(x)+(x-6)=ln(6x) | | -1/2+3/5= | | 7/10+7/10= | | 13x+5=x+3 | | Y=-3x+-2 | | -6x(3x-1)=0 | | 13x+5=x-23 | | X(x(1.23))=271 | | 9x+11=3x+29 | | 3/10-2/5= | | 24/25-3/5 | | Log[5](3-2x)=1 | | (6-(1)-3)-(6(3)-3)/(1-(3)) | | X+18+x-34=180 | | X^2+y^2+16x-20y+10=0 | | (4-9x)(2+5x)=0 | | 2x-1+8x-29=180 | | 6y-1=25-y | | 6/24=p/36 | | x^2-2x+5-4y=0 | | x-19+4x-11=180 | | (k*k)-8k=0 | | 14x+12+11x-7=180 | | (4n+4)=(3n-4) | | k/50=9/30 | | 7x+26+3x-6=180 | | 6(5x-4)=17x+15 | | 8x-23=3x+7 | | 6/x=10/35 | | u/14=v | | X=6y-14 | | 210+0.25x=360 |